2016
DOI: 10.1038/bjc.2016.189
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic colorectal cancer: microbial contributors to disease prevention, development and therapy

Abstract: The gut microbiota has been hailed as an accessory organ, with functions critical to the host including dietary metabolic activities and assistance in the development of a proper functioning immune system. However, an aberrant microbiota (dysbiosis) may influence disease processes such as colorectal cancer. In this review, we discuss recent advances in our understanding of the contributions of the microbiota to prevention, initiation/progression, and treatment of colorectal cancer, with a major focus on biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 66 publications
(78 reference statements)
2
88
1
Order By: Relevance
“…In each of these cancers, the oral and/or the gut microbiota have been postulated to contribute to cancer pathogenesis. The detailed mechanisms underlying microbe-host interactions in carcinogenesis, usually derived from in vivo murine models, are beyond the scope of this review but have been discussed elsewhere (2, 3, 12). Instead, we will focus on summarizing the available human epidemiological data and discuss the next potential steps in translational research to understand the interaction between the microbiota and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In each of these cancers, the oral and/or the gut microbiota have been postulated to contribute to cancer pathogenesis. The detailed mechanisms underlying microbe-host interactions in carcinogenesis, usually derived from in vivo murine models, are beyond the scope of this review but have been discussed elsewhere (2, 3, 12). Instead, we will focus on summarizing the available human epidemiological data and discuss the next potential steps in translational research to understand the interaction between the microbiota and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental data show how potential colorectal cancer (CRC) driver bacteria such as enterotoxigenic Bacteroides fragilis (ETBF), Fusobacterium nucleatum, colibactin-producing Escherichia coli (CPEC) and Porphyromonas, damage mucosal barrier functions by degrading mucins, damaging intercellular junctions and cellular DNA. Direct bacterial actions and immunological responses may induce dysplasia and carcinogenesis [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently emerged that factors beyond tumor genomics influence cancer development and therapeutic responses (47), including host factors such as the gastrointestinal (gut) microbiome (810). A number of studies have shown that the gut microbiome may influence anti-tumor immune responses via innate and adaptive immunity (11, 12), and that therapeutic responses may be improved via its modulation (13, 14), however this has not been extensively studied in cancer patients.…”
mentioning
confidence: 99%